Level of knowledge, attitudes, practices and infestation of Aedes Aegypti - Paiva Quesquén, José Antonio (2018)
The present investigation refers to the objective of determining the level of knowledge, practices and practices on dengue and the levels of Aedes aegypti infestation in the town of Motupe. Department of Lambayeque, June 2017. A descriptive and cross-sectional analytical study is carried out, through a cut in time, where the following variables are shown: knowledge, attitudes and practices directly or indirectly in the time of the study. The sample in the study was chosen at random, fulfilling the inclusion and exclusion criteria and permanently residing in the area, where there is a total of 120 homes. It was found that the level of knowledge about dengue was 25%, the level of knowledge being high level, and the highest percentage was of the Medium level with 40%. The level of attitudes, has found that 13.3% good level, being the highest percentage of indifferent with 57.5%. The level of practices on dengue, it has been found that 28.3% have a level of good practices, but the percentage of weight has increased by 71.7%, with the level of infestation being 6.7%. It was shown that 25%, and the attitude was 57.5%. It showed the indifference of the community and the collaboration in this public health problem. Likewise, the level of practices was 71.7% (deficient), where the neglected population evidenced the practices in favor of preventing the epidemic.